Barriers for physical activity in Primary Health Care - Gomes, Grace Angélica de Oliveira; Papini, Camila Bosquiero; Nakamura, Priscila Missaki [UNESP]; Teixeira, Inaian Pignatti [UNESP]; Kokubun, Eduardo [UNESP] (My University, 2019)
The objective of the study was to compare the barriers to physical activity (PA) between women participants and nonparticipants of an exercise program in Primary Health Care. Cross‐sectional study carried out in areas covered by health centers that offered an exercise program. Twenty‐two participants and non‐participants of the programs were selected and evaluated in relation to sociodemographic characteristics, PA and barriers. Descriptive and comparative data analyzes were performed. The most reported barriers for women non‐participants were lack of company (40.9%), lack of energy (38.7%), feeling very tired or unmotivated (38.2%). The non‐participants and the elderly had a higher proportion of barriers to PA.
Barreiras para prática de atividade física entre mulheres atendidas na Atenção Básica de Saúde
Keywords: Exercise; Prevention; Primary Health Care; Public health